Early Postnatal Stress Impairs Cognitive Functions of Male Rats Persisting Until Adulthood - Holubová, Anna; Lukášková, Ivana; Tomášová, Nikol; Šuhajdová, Mária; Šlamberová, Romana (Frontiers in Behavioral Neuroscience, 2018)
Methamphetamine (MA) is the most abused “hard” illicit drug in the Czech Republic. Drugs abused during pregnancy are not hazardous merely to the mother, but also to developing fetuses. The offspring of drug-addicted mothers are also often exposed to perinatal stressors that may impair brain development of affected progeny. The present study examines the effect of perinatal stressors and drug exposure on cognitive function in male progeny. In the present study, rat mothers were divided into three groups according to drug treatment during pregnancy: controls (C); saline (SA, s.c., 1 ml/kg); MA (s.c., 5 mg/ml/kg). Litters were divided into two groups according to postnatal stressors: non-stressed controls (N); maternal separation (S). For evaluation of learning and memory, adult male progeny were tested in the Morris Water Maze (MWM). Our results revealed no significant effects caused by prenatal drug or prenatal stress exposure. On the other hand, chronic postnatal stress, mediated by maternal separation, significantly impaired learning on the Place Navigation test. In addition, maternal separation was associated with changes in search strategies on the Place Navigation, Probe, and Memory Recall tests. Specifically, postnatal stress increased thigmotaxis, indicating less awareness of the hidden platform. In conclusion, the present study provides evidence that exposure to early postnatal stress significantly impairs cognitive functions of male rats, which persists into adulthood.